Value-in-context in Crowd-funding ecosystems: how context frames value co-creation - Quero-Gervilla, María José; Kelleher, Carol; Ventura-Fernández, Rafael (My University, 2014)
The aim of the present paper is to analyse if the phenomenon of crowd funding can be considered a service ecosystem, where all of the actors generate resources and co-create value for and within the system. A qualitative, multiple case base approach is used to analyze six crowd-funding initiatives in the Spanish arts sector. The findings reveal seven types of value co-creation and six actors that interact on three levels: micro–meso–macro, illustrating that crowd-funding can be considered a service ecosystem that frames value co-creation. We conclude with a discussion of the findings, managerial implications and future research opportunities.
Keywords: Empresas - Gestión; Empresas - Finanzas; Service ecosystems; Network; Crowd-funding; Service-dominant logic; Co-creation